The financial crisis, rethinking of the global financial architecture, and the trilemma - Joshua Aizenman; Menzie D. Chinn; Hiro Ito (Asian Development Bank Institute (ADBI), 2010)
This paper extends our previous paper (Aizenman, Chinn, and Ito 2008) and explores some of the unexplored questions. First, we examine the channels through which the trilemma policy configurations affect output volatility. Secondly, we investigate how trilemma policy configurations affect the output performance of the economies under severe crisis situations. Thirdly, we look into how trilemma configurations have evolved in the aftermath of economic crises in the past. We find that trilemma policy configurations and external finances affect output volatility mainly through the investment channel. While a higher degree of exchange rate stability could stabilize the real exchange rate movement, it could also make investment volatile, though the volatility-enhancing effect of exchange rate stability on investment can be cancelled by holding higher levels of international reserves (IR). Greater financial openness helps reduce real exchange rate volatility. These results indicate that policymakers in a more open economy would prefer pursuing greater exchange rate stability and greater financial openness while holding a massive amount of IR. We also find that the crisis economies could end up with smaller output losses if they entered the crisis situation with more stable exchange rates or if they continue to hold a high level of IR and maintain greater exchange rate stability during the crisis period. Lastly, we find that developing countries are often found to have decreased the level of monetary independence and financial openness, but increased the level of exchange rate stability in the aftermath of a crisis, especially for the last two decades. This finding indicates how vulnerable developing countries, especially emerging market ones, are to volatile capital flows as a result of global financial liberalization.
Keywords: F15; F21; F31; F36; F41; O24; 330; Internationales Finanzsystem; Finanzmarktkrise; Weltwirtschaftsordnung; Internationaler Finanzmarkt; Wirtschaftliche Anpassung; Kapitalmarktliberalisierung; Wirkungsanalyse; Welt